Carrageenan Concentration And Growth Of Kappaphycus alvarezii Seaweed In Liang Village, Banggai Regency, Central Sulawesi Province - Sangkia, Frederik Dony; Pattirane, Chrisoetanto P.; Ramli, Taufik Hadi (Jurnal Ilmiah Platax, 2024)
This study aimed to assess the quality of seaweed by analyzing its carrageenan content, water content, and growth rate. The research was conducted in the waters of Liang Village and Jayabakti Village for 45 days, with observation periods every 15 days. Carrageenan examination was carried out at the Pharmacy Laboratory of Sam Ratulangi University, while the water content was determined at the THP Laboratory of the same university. Growth measurements were conducted at 0, 15, 30, and 45 days in both locations. The results showed that the concentration of carrageenan in seaweed from Jayabakti Village was 39.81%, while in Liang Village it was 35.88%. The percentage of seaweed water in Liang Village was 9.3%, while in Jayabakti it was 27.0%. In addition, there was no significant difference in seaweed growth between the two water sites (P>0.05). The average difference in seaweed growth between Jayabakti Village and Liang Village on days 15, 30, and 45 was 1.5, 0.5, and 16.3, respectively. The daily weight gain rate of seaweed on day 15 was 5.55% in Jayabakti Village Waters and 5.50% in Liang Village Waters. On the 30th day, the daily weight gain of seaweed in Jayabakti Village Waters and Liang Village was 4.88% and 4.89%, respectively. On the 45th day of the rearing period, seaweed in Jayabakti Village Waters experienced a weight gain of 4.16%, while seaweed in Liang Village experienced a weight gain of 4.22%. The findings showed that the carrageenan test, conducted by assessing water content, indicated that the quality of seaweed in the waters of Liang Village was superior to that of Jayabakti Village. Keywords: carrageenan, growth, Jayabakti village, Liang village, water content